Cross hedging stock sector risk with index futures by considering the global equity systematic risk - Wen-Chung Hsu; Hsiang-Tai Lee (International Journal of Financial Studies, 2018)
This article investigates the effectiveness of TAIEX (Taiwan Stock Exchange) futures, Taiwan 50 futures, and nonfinance nonelectronics subindex (NFNE) futures for cross hedging the price risk of stock sector indices traded on the Taiwan stock exchange. A state-dependent volatility spillover GARCH hedging strategy is developed to capture the regime switching global equity volatility spillover effect. Empirical results show that the NFNE futures exhibit superior effectiveness as an instrument for hedging stock sector exposures compared with the TAIEX and Taiwan 50 futures. Simultaneous hedge using both NFNE and MSCI (Morgan Stanley Capital International) world index futures further improves the hedging effectiveness compared with the hedging strategy using only the NFNE futures. This shows the importance of hedging the global equity systematic risk of stock sectors by considering the comovement between domestic and global equity markets.
Keywords: C32; C51; G10; 330; Markov regime switching; multiple futures hedging; volatility spillover; multivariate; GARCH; cross hedging